PENINGKATAN KEMAMPUAN BACA TULIS AL-QUR’AN MELALUI PROGRAM BINA BACA QUR’AN (BBQ) PADA PESERTA DIDIK DI SMA YP UNILA BANDAR LAMPUNG - apriliawati Wati; Damanhuri Damanhuri; Agus Susanti (Jurnal Bilqolam Pendidikan Islam, 2026)
High school students’ ability to read and write the Qur’an remains relatively low, particularly in mastering tajwid, the correct articulation of Arabic letters (makhārij al-ḥurūf), tartil, waqaf rules, reading fluency, and the accurate writing of Arabic script and vowel marks. This condition was reflected in the pre-cycle assessment results, which showed an average score of 63.57 with a learning mastery rate of only 28.57%, far below the Minimum Mastery Criteria (KKM) of 80. These findings indicate the need for an effective and systematic learning program to improve students’ Qur’anic literacy skills. Therefore, this study aimed to enhance students’ ability to read and write the Qur’an through the implementation of the Quranic Reading Development Program (BBQ). This study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. Data were collected through tests, classroom observations, interviews, and documentation, while data analysis was carried out using a quantitative descriptive approach. The findings demonstrated a gradual and significant improvement in students’ competencies. In Cycle I, the average score increased to 67.57 with a mastery rate of 37.14%. Furthermore, in Cycle II, students showed substantial progress, achieving an average score of 88.14 with a mastery rate of 80%, which exceeded the predetermined KKM. Thus, the BBQ program proved to be effective in improving students’ Qur’anic reading and writing skills in a gradual, structured, and sustainable manner.